The cadmium decontamination and disposal of the harvested cadmium accumulator Amaranthus hypochondriacus L. (January 2022) - Lei, Long; Cui, Xiaoying; Li, Cui; Dong, Meiliang; Huang, Rong; Li, Yongxing; Li, Yingwen; Li, Zhian; Wu, Jingtao
Abstract: The heavy metal accumulated biomass after phytoremediation needs to be decontaminated before disposal. Liquid extraction is commonly used to remove and recycle toxic heavy metals from contaminated biomass. In this study, we examined the cadmium (Cd) removal efficiency using different chemical reagents (hydrochloric acid, nitric acid, sulfuric acid, and ethylenediaminetetraacetic acid disodium) of the post-harvest Amaranthus hypochondriacus L. biomass. The purifications for the extracted liquids and ecological risk assessments for the extracted residues were also investigated. We have found that 77.8% of Cd in stems and 62.1% of Cd in leaves were removed by 0.25 M HCl after 24 h. In addition, K2 CO3, KOH, and 4 Å molecular sieve could remove ≥89.0% of Cd in the extracted liquids. Finally, after we returned the extracted residues to the earthworm-incubated soil, the extracted biomass negatively affected the growth (weight loss ≥ 11.0%) and survival (mortality ≥ 33.3%) of Eisenia fetida . It should be noted that earthworms decreased soil available Cd concentrations from 0.14–0.05 mg kg −1 to 0.11–0.04 mg kg −1 and offset the negative effects of the Cd-contaminated biomass on soil microbes. Overall, given the cost of reagents, the Cd removal efficiency, and the ecological risks of the extracted biomass, using 0.25 M HCl for liquid extraction and K2 CO3 for purification should be recommended. This work highlights the potential of liquid extraction for immediately and directly removing the Cd from fresh contaminated accumulator biomass and the resource cycling potential of the extracted liquids and biomass after purification. Graphical abstract: Image 1 Highlights: Liquid extraction for Cd removal of A. hypochondriacus L. biomass was evaluated. 62.1–77.8% of Cd in biomass were removed by 0.25 M HCl after 24 h. K2 CO3, KOH, and 4 Å molecular sieve were effective to remove Cd from waste liquids. Extracted liquid after purification using K2 CO3 was potential to use as a fertilizer. Earthworms reduced detriments of Cd-containing biomass for soil microbes.